EKSPLORASI JAMUR MAKROSKOPIS DI HUTAN OELUAN KABUPATEN TIMOR TENGAH UTARA - Lukas Pardosi; Florian Mayesty Prima Makin; I Gede Arya Wiguna (Fakultas Pertanian, Universitas Timor, 2020)
Research on the diversity of macroscopic fungi in the Oeluan Forest area of ​​North Central Timor district has never been reported. This research was conducted in January 2020 with a geographical location of 9° 2¢ 48